2019
DOI: 10.1016/j.cegh.2018.06.004
|View full text |Cite
|
Sign up to set email alerts
|

APRI score non-invasive marker of metabolic syndrome in breast carcinoma patients

Abstract: Background: Breast carcinoma is one of the commonest cancer in women accounting for major health burden worldwide. Metabolic syndrome is a known risk factor of non-alcoholic steatohepatitis (NASH) as well as breast carcinoma. APRI (Aspartate aminotransferase to platelet ratio index), a known non-invasive marker of liver fibrosis and steatohepatitis has never been studied in patients of metabolic syndrome with breast carcinoma. Breast carcinoma has various modifiable risk factors such as obesity and alcohol con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
(23 reference statements)
0
0
0
Order By: Relevance
“…Verma et al found that APRI scores were significantly higher in patients with breast carcinoma with MetS [ 29 ]. De Matteis et al demonstrated that high APRI scores significantly correlate with increased cardiovascular risk, particularly in females, supporting our findings [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Verma et al found that APRI scores were significantly higher in patients with breast carcinoma with MetS [ 29 ]. De Matteis et al demonstrated that high APRI scores significantly correlate with increased cardiovascular risk, particularly in females, supporting our findings [ 30 ].…”
Section: Discussionmentioning
confidence: 99%